Estimation of effect of breeding bulls and genetic parameters on early growth performance of calves at farm and field levels (Bangladesh Journal of Animal Science, 2013)
The present study was conducted using records on four breeding bulls maintained at the Artificial Insemination (AI) Center of Bangladesh Agricultural University (BAU), Mymensingh and on 154 of their progeny maintained at BAU Dairy Farm (112) and some villages (42 progeny) adjacent to BAU for estimating the effect of breeding bulls and genetic parameters on early growth performance of the progeny at farm and field levels. Genetic correlations between traits of bulls and their progeny were also estimated. Bull traits were metabolic body weight (MWT), feed intake (FI) and residual feed intake (RFI) where progeny traits were birth weight (BWT), final body weight (FWT) at 90 days of age and average daily gain (ADG). Mean BWT of progeny at farm and field level was 16.34±1.85 to 17.62±1.97 kg and 13.89±2.78 to 16.11±2.98 kg, respectively. The FWT at farm progeny was 48.9±2.87 to 55.67±2.14 kg whereas 43.43±2.50 to 52.22±3.34 kg for field progeny. The ADG at farm and field progeny was 0.36±0.03 to 0.43±0.01 and 0.32±0.03 to 0.42±0.03 kg, respectively. The BWT and FWT of farm progeny were significantly (p>0.05) higher than the progeny of field level. Breeding bulls had significant (p